Pain and Catastrophizing in Patients With Rheumatoid Arthritis: An Observational Cohort Study. Issue 5 (August 2019) - Cohen, Ezra M.; Edwards, Robert R.; Bingham, Clifton O.; Phillips, Kristine; Bolster, Marcy B.; Moreland, Larry W.; Neogi, Tuhina; Marder, Wendy; Wohlfahrt, Alyssa; Clauw, Daniel; Lee, Yvonne C.
Abstract : Background: The aims of this study were to define changes in catastrophizing that occur with initiation of a new disease-modifying antirheumatic drug (DMARD) and to examine the relationship between changes in Clinical Disease Activity Index (CDAI) and changes in catastrophizing. Methods: Participants in an ongoing multisite, observational study completed the Pain Catastrophizing Scale (PCS) before and 12 weeks after DMARD initiation. We used multivariable linear regression models to examine the association between changes in CDAI as the exposure and change in pain catastrophizing as the outcome. We also assessed the relationship between changes in each component of CDAI and change in PCS, using multivariable linear regression models. Results: Among the 165 rheumatoid arthritis patients with data on CDAI at both time points, CDAI decreased from 22 to 11.5 on a 76-point scale ( p < 0.0001) after 12 weeks. Pain intensity decreased from a median of 5 to 3 on a 10-point numeric rating scale ( p < 0.0001), and catastrophizing decreased, from 16.0 to 12.0 on the 52-point PCS ( p = 0.0005). Among the 163 with complete data for the regression analysis, changes in CDAI were positively correlated with changes in catastrophizing (standardized β = 0.19, p = 0.01). Of the components of the CDAI, change in assessor global score was most strongly associated with changes in catastrophizing (standardized β = 0.24, p = 0.003). Conclusions: Pain catastrophizing decreases, in conjunction with disease activity, after initiation of a new DMARD. These findings provide support for catastrophizing as a dynamic construct that can be altered with treatment directed at decreasing inflammatory disease activity and pain.